The art of compassionate business : main principles for the human-oriented enterprise - Cignacco, Bruno Roque (Productivity Press, 2019)
There are several well-ingrained assumptions regarding the dynamics of work and business activities, which can be refuted. Some examples of these widespread assumptions in the business and work environments are: employees being viewed as commodities, competitors perceived as threats, companies' resources seen as limited, and customers perceived as scarce and difficult, etc. All which leads to the question, "Is there a way to perform business activities more humanely?" This book challenges the reader to change the way they perform in business situations and become more focused on the human aspects of business activities. The users of this knowledge and those affected by them will undergo a profound transformation in the way they perform business activities. They will benefit from gradually testing and implementing the guidelines conveyed in this book, both in the business environment and the workplace. When readers put these principles into practice, positive ripple effects are bound to affect other stakeholders of the organization they work for or own. This book includes aspects related to mission and vision, passion, business mindset, organizational learning, improvement of business conversations, use of constructive criticism and improvement of relationships with the most relevant stakeholders (customers, suppliers, intermediaries, community, and employees, etc.). The book also includes a discussion of creativity and the innovation process, as well as other factors that create a healthy business environment. Extensive appendices include topics such as negotiation, marketing, use of social media and others